Note on the Ogam and Latin Inscriptions from the Isle of Man, and a recently found Bilingual in Celtic and Latin - Kermode, P M C (Proceedings of the Society of Antiquaries of Scotland, 1911)
A brief account of the previously published Latin and Ogam inscriptions on the Isle of Man is accompanied by illustrations. The new discovery from Knoc y doonee, has the first example of a bilingual inscription in Ogam and in Roman capitals from the island. It is a large pillar of clay slate. The fact of the pillar having its edges dressed shows that this cannot be a monument of the earliest period; but the inflexions in the Celtic inscription and the plain capitals and whole character of the Latin one, are, with the forms of the names, in keeping with the idea that it may belong to the first half of the sixth century.